Effects of Land Use and Climate Change on Siamese Eld's Deer (Rucervus eldii siamensis) Distribution in the Transboundary Conservation Area in Thailand, Cambodia, and Lao PDR - Trisurat, Yongyut; Bhumpakphan, Naris (Frontiers in Environmental Science, 2018)
The Emerald Triangle Protected Forests Complex (ETFC) is recognized as a globally outstanding area for transboundary biodiversity conservation. Eld’s deer (Rucervus eldii) include three subspecies; R. eldii siamensis, R. eldii eldii, and R. eldii thamin. This research focused on Siamese Eld’s deer (R. eldii siamense), which is one of the 10 critically endangered vertebrates found in the ETFC. Its habitats are threatened by forest conversion to agriculture and human settlements, as well as by future climate change. The objectives of this article were to predict Siamese Eld’s deer distribution and to determine potential shifts in its suitable habitat as the results of different land use and climate change scenarios in 2030. Occurrence data for Siamese Eld’s deer were gathered from literature and field surveys. The Maximum Entropy (Maxent) and logistic regression models were used to generate suitable habitats. The model that generated the greatest accuracy was selected for distribution mapping. The results showed 142 records of Siamese Eld’s deer. The predicted distribution map generated from the logistic regression model provided greater accuracy (90%) than the Maxent (80%). The predicted habitats of Siamese Eld’s deer covered 6.0% of the ETFC landscape by 2013. They were concentrated in the protected areas of the lowland forests of Cambodia and Lao PDR. The land use change only did not affect the distribution of Siamese Eld's Deer, but climate change would impact the distribution substantially. In addition, the combination of all future land use and climate changes would significantly reduce the current habitat to approximately 2.6% of the ETFC landscape, which is a decline 58.0%. The lowest extent of 2.5% was predicted for the combination of unsustainable land use and climate change scenario. Recommendations on biodiversity conservation cooperation among the three countries, habitat protection and ex-situ conservation were proposed.